Scene perception from central to peripheral vision - Loschky, Lester C.; Nuthmann, A.; Fortenbaugh, F. C.; Levi, D. M. (My University, 2017)
When we view a real-world scene with both eyes, we see a seamless vista that covers a visual field of more than 200° diameter horizontally and 125° vertically. The entire scene generally appears to have high resolution, contrast, and color saturation, despite the dramatic changes in the optics, anatomy, and physiology of our eyes and visual pathways as the retinal images shift from the center of gaze to the periphery. Thus, a key issue in real-world scene perception is the roles played by central and peripheral vision. Central vision has the highest visual acuity and is where we pay the most attention to objects of interest. However, since central vision only extends out to a radius of roughly 5° around fixation, peripheral vision is the vast majority of our visual field. Yet, the nature of peripheral vision is mysterious, in that our common intuitions about it are often wrong. For example, most people appear to be quite unaware of the limitations of peripheral vision (Lau & Rosenthal, 2011). This is shown by how surprising viewers find demonstrations of the loss of visual resolution with eccentricity, such as failure to detect even roughly calibrated increasing blur with eccentricity using the Geisler and Perry (1998) algorithm (for a demonstration of this, see https://youtu.be/9DTHVRhBcQ0). Conversely, many people would probably be surprised to know that while driving it is possible to maintain one's lane position using only peripheral vision even while using central vision for an attentionally demanding visual task located 30° below the dashboard (Summala, Nieminen, & Punto, 1996). (Importantly, however, consistent with what one might expect, under the same conditions, drivers are also very poor at noticing potential crash hazards, such as when a car in front of them suddenly slows down—thus, driving using only peripheral vision is very dangerous [Summala, Lamble, & Laakso, 1998].)
Citation: Loschky, L. C., Nuthmann, A., Fortenbaugh, F. C., & Levi, D. M. (2017). Scene perception from central to peripheral vision. Journal of Vision, 17(1), 5. doi:10.1167/17.1.6
Keywords: Central Vision; Peripheral Vision; Fovea; Periphery; Scene Perception; Retinal Eccentricity